2006
DOI: 10.1111/j.1600-0838.2006.00572_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of passive mobilization exercise on improvement of muscle regeneration and prevention of fibrosis after laceration injury of rat

Abstract: OBJECTIVE: To evaluate the muscle healing effect of passive mobilization exercises after a laceration injury. DESIGN: Randomized‐controlled trial. SETTING: Basic science laboratory. ANIMALS: Male Sprague–Dawley rats (N=36), age ranging from 8 to 10 weeks and weight ranging from 300 to 400 g. INTERVENTION: The bilateral gastrocnemius muscles were lacerated. The left‐leg muscles were used as the study groups and the right side was used as the control (lacerated muscles without any treatment, n=8). In the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…The full recovery of muscle weight only 21 days after injury in Act rats appeared then as a striking result, all the more noteworthy as morphological data clearly showed that this was achieved by the development of myofibers, with less fibrosis development than in Reg muscles of Sed rats. These results strengthen previous observations that suggested that physical activity ensured to limit the appearance of connective tissue in Reg muscles (23).…”
Section: Discussionsupporting
confidence: 82%
“…The full recovery of muscle weight only 21 days after injury in Act rats appeared then as a striking result, all the more noteworthy as morphological data clearly showed that this was achieved by the development of myofibers, with less fibrosis development than in Reg muscles of Sed rats. These results strengthen previous observations that suggested that physical activity ensured to limit the appearance of connective tissue in Reg muscles (23).…”
Section: Discussionsupporting
confidence: 82%
“…Not only does the contractile activity decrease in the immobilized muscle, but there is also a mechanical load decrease. This also affects the proliferation of this tissue, once it regulates the production of growth factors and collagen synthesis 22 . In this sense, fibroblasts, which are subject to active and passive muscular tension, have their metabolism altered with the decreases of tension caused by immobilization, which incurs in area density increases of the intramuscular connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This particular growth factor is stimulatory to collagen and ECM deposition that can be detrimental to the skeletal muscle regeneration process, contributing to exacerbated fibrosis and loss of contractile properties [32]. When TGF-β1 activity is inhibited by the action of decorin, regeneration indexes significantly improve and fibrosis development decreases by 50% in laceration injuries [133], conveying toward in vitro observations [132]. TGF-β1 acts on myoblasts, leading to the overexpression of fibrosis-related proteins and the down-regulation of myogenic proteins (desmin, MyoD, and myogenin).…”
Section: The Role Of Growth Factors and Cytokines In Skeletal Muscle mentioning
confidence: 99%